Molecular footprint and pathways of DOM biotransformation in the Yangtze River - Guangrui Yang; Farong Chen; Songchol Kang; Jiaming Chen; Chu Zhao; Lize Meng; Xinyi Zhang; Jiayue Lu; Shuaidong Li; Zihao Bian; Jian Zhou; Qihao Jiang; et al. (Water Research, 2026)

Origin of Early Cretaceous magmatism and its linkage with Cu–Fe–Au skarn mineralization in the Tonglushan ore field, eastern China: Evidence from whole-rock, zircon, and apatite geochemistry - Ming Zhang; Xiangzhou Li; Yanyan Zhao; Shichao Shang; Jiaming Zhou; Wan Huang; Yiheng Liu; Ziqing Yan; Xiaoyang Liu; Jun Tan (Lithos, 2026)

Constant-voltage triboelectric nanogenerator coupled with an intermittent speed-up mechanism and bionic jellyfish blades for low-speed water flow energy harvesting - Chenxi Li; Yongle Zhou; Fupu Xie; Jiaming Zhang; Yi Li; Hongwei Wang; Kaisheng Li; Zihao Li; Siyuan Liu; Tianyu Li (Chemical Engineering Journal, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

Cyclic biomineralization by incorporating iron-oxidizing and sulfate-reducing microorganisms for sustainable iron removal and sulfur recovery from acid mine drainage: Efficiency and mechanism - Xingjie Wang; Ling Liu; Yuxuan Yang; Jiaming Du; Liyuan Ma; Jie Tang; Peng Liu; Jianwei Zhou (Minerals Engineering, 2026)

Dynamic Tensile Properties and Fracture Evolution Characteristics of Ice-Filled Fissured Red Sandstone - Jiaming Wang; Zilong Zhou; Lingyi Zeng; Jun Hou; Zhen Wang (Rock Mechanics and Rock Engineering, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Catchment land use shapes lake-atmosphere thermal contrast and synchrony globally - Zhirong Yu; Gang Li; R. Iestyn Woolway; Jixiang Yang; Jiaming Hu; Juan Tao; Kun Shan; Kun Shi; Yunlin Zhang; Lian Feng; Erik Jeppesen; Qichao Zhou (Science Bulletin, 2026)

Decoding the hidden resistome: Single-cell Raman detection of viable but non-culturable antibiotic-resistant bacteria in aquatic environments - Tong Zhou; Linyi Fan; Hao Yang; Jiaming Zhang; Jingshuang Cui; Jiao Qu; Ya-nan Zhang (Journal of Hazardous Materials, 2026)

Garnet microtextures and geochemistry of the Tonglushan Cu–Fe–Au skarn deposit (Edong district): Constraints on fluid evolution and skarn mineralization - Ming Zhang; Xiangzhou Li; Ziqing Yan; Shichao Shang; Wan Huang; Yanyan Zhao; Jiaming Zhou; Xiaoyang Liu; Jingui Huang; Jun Tan (Journal of Geochemical Exploration, 2026)

Auxiliary fermentation with Pediococcus acidilactici C1 reshapes flavor formation in sufu: An integrated metagenomic, flavoromic and non-targeted metabolomic deciphering - Chen Chen; Jiaming Li; Feng Wang; Mei Cheng; Tao Sheng; Zahoor Ahmed; Jingwei Hu; Yibin Zhou (Food Chemistry, 2026)

Defined co-fermentation of Kluyveromyces marxianus and lactic acid bacteria enhances bioactivity and aroma formation in black tea kombucha - Aiping Yao; Jiaming Li; Yuanyuan Zhao; Tianzhi Qu; Yan Geng; Lingxi Zhou; Anqi Chen; Jian Chen (Food Bioscience, 2026)

A bibliometric analysis of global duckweed research (2015–2025): research trends, international collaborations, and emerging themes - Jiaming Wang; Zhenghong Peng; Zuoyue Duan; Yaojun Zhou; Hongling Zhu; Shijun You; Zhiyi Peng; Mengni Shi; Qulian Guo; Wenjun Liu; Ling Guo (Hydrobiologia, 2026)

Collaborative scheduling of shared electric vehicle charging stations - Fangting Zhou; Balázs Kulcsár; Jiaming Wu (Transportation Research Part D: Transport and Environment, 2026)

Dynamic Mechanical Response and Stress Wave Propagation Characteristics of Red Sandstone with Ice-Filled Joints of Varying Thicknesses - Zilong Zhou; Jiaming Wang; Zhen Wang; Yingxin Zhou; Ziyu Wang (Rock Mechanics and Rock Engineering, 2026)

Fully coupled numerical model of moored structures-mooring line-ice ridge interaction - Jiaming Chen; Shengjie Rui; Sen Han; Shifeng Ding; Jie Tan; Li Zhou (Ocean Engineering, 2026)

Evaluation of Groundwater Origin, Quality, and Potential Health Risks in the Ordos Coal Mine Base, Northwest China: Insights from Geochemical and Isotopic Approaches - Jiaming Zhou; Keyi Zhang; Tenglin Deng; Zilong Liao; Bing Xu; Fei Gao; Quandong Lian; Jianghong Yan; Shen Qu (Mine Water and the Environment, 2026)

A new matrix propagation method for theoretical analysis of wave propagation in low-temperature gradient layered rock mass with parallel ice-filled joints - Jiaming Wang; Zilong Zhou; Zhen Wang; Jun Hou; Ning Yang; Yaocai Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

Research on the Support Mechanism of Tunnel Anchor Bolt Based on Physical Model Experiments and Continuous–Discontinuous Theory - Mingyi Wang; Shaobo Chai; Bo Hu; Chen Xu; Jiaming Wu; Yongqiang Zhou; Xiaodong Fu (Rock Mechanics and Rock Engineering, 2026)

Investigation of CO2 absorption and desorption performance and mechanism of aqueous [TETAH][Im] in a PTFE hollow fiber membrane contactor - Chunyun Zhou; Yanbin Yun; Chang Li; Jia Liu; Jiaming Mao; Wenjuan Yang; Haiyan Huang; Guoqiang Zhuang; Meng Li (Journal of Environmental Chemical Engineering, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Identification of electromechanical participation matrices via scaled-derivative DMDc for improved PPF active vibration control of thin-walled structures - Qinshan Ouyang; Longlei Dong; Jian Liu; Jiaming Zhou (Engineering Structures, 2026)

Environmental exposure to bisphenol S suppresses white adipocyte beiging and energy expenditure via CYP2E1 in mice - Qi Liu; Yuancheng Shao; Jiaming Xue; Yicheng Jiang; Shuai Chen; Dongmei Wang; Yan Zhou; Jie Zhao; Wei Gao; Liming Tang (Environmental Pollution, 2026)

Hybrid framework combining machine learning with mechanism models for enhanced forecasting of biomass gasification products - Jiaming Song; Zongqi Chen; Haining Tang; Hong Ding; Shiliang Wu; Zhou Liu; Feng Gong (Bioresource Technology, 2026)

Experimental investigation of phase lag in compound channels under repeated unsteady flow cycles - Jiaming Liu; Yang Xiao; Carlo Gualtieri; Huanfeng Duan; Jieqing Liu; Jian Zhou (Journal of Hydrology, 2026)

Post-mortem analysis of degradation behavior in catalyst layers of proton exchange membrane fuel cell under near-water boiling temperature - Daijun Yang; Bo Zhou; Yirui Lu; Jiaming Lou; Bing Li; Pingwen Ming (Fuel, 2026)

Multifactorial synergistic strategies mediate the biocontrol of Fusarium oxysporum-induced root rot by Bacillus velezensis SYL-3 - He Liu; He Huang; Yuzhe Wang; Mengnan An; Jiaming Bai; Jianquan Zhou; Haiyang Lan; Aiwei Qi; Baoan Song; Yuanhua Wu (Pesticide Biochemistry and Physiology, 2026)

Evaluating aeration rate modulation to restructure denitrifier communities for nitrous oxide mitigation in cattle manure composting using a novel integrated analytical framework - Yu Sun; Xiran Zhou; Jiaming Fan; Lei Sun; Shuai Shi; Xiuhong Xu (Journal of Environmental Management, 2026)

Integrated network toxicology, molecular docking and transcriptomics reveal the mechanistic role of phthalate esters in metabolic disease pathogenesis - Yuancheng Shao; Qi Liu; Yicheng Jiang; Gang Zhou; Xihan Gu; Shufan Zhang; Shuai Chen; Jiaming Xue; Liming Tang (Food and Chemical Toxicology, 2026)

Post-mortem analysis of the degradation behavior of the fuel cell gas diffusion layer under near to water boiling point conditions - Yirui Lu; Daijun Yang; Jiaming Lou; Bo Zhou; Xiangyang Zhou; Xiangmin Pan; Bing Li; Pingwen Ming (Chemical Engineering Journal, 2026)

Analysis of large deformation characteristics of deep foundation pit at a subway station constructed by the tunnel-before-station method - Jiaming Liang; Wenji Su; Tingjin Liu; Huifeng Wu; Lele Lu; Huashan Zhong; Shuyang Zhou (European Journal of Environmental and Civil Engineering, 2025)

Extreme precipitation amplified the cumulative effects of DOM availability on organic-sourced DIC in the Yangtze River - Chu Zhao; Guangrui Yang; Lize Meng; Heran Chen; Shuaidong Li; Farong Chen; Zihao Bian; Jiaming Chen; Jian Zhou; Qihao Jiang; Tao Huang; Hao Yang; et al. (Water Research, 2025)

Integrated improved ant colony optimization and Q-learning for ice navigation route planning - Jiaming Zhou; Xiuwen Liu; Hongshuai Xie; Yong Yin (Ocean Engineering, 2025)

The effect of hydroxyl groups and humidity on the adsorption capacity of amine-functionalized macroporous resins for direct air capture - Jiaming Wang; Xiaohan Weng; Tao Han; Yongqiang Wang; Jinning Yang; Chao Zhou; Dong Xu; Liying Liu (Chemical Engineering Journal, 2025)

Phenytoin quaternary ammonium salt is a novel wound treatment drug with both pro-healing and antibacterial effects - Yuchen Li; Jiaming Cui; Peihui Zhou; Bixuan Cao; Li Zhao; Weize Kong; Xueheng Sun; Ya Fang; Jinwu Wang; Mingzhi Song; Li Wang (Chemical Engineering Journal, 2025)

A Novel Approach for Fast Microplastic Quantification in Sediments Using Machine Learning—Spectrometer Combinations - Piao Yao; Jiaming Zhang; Bin Zhou; Yang Chen; Ding He (Water, Air, & Soil Pollution, 2025)

Umami_IP: An integrated model and explanatory analysis for quantitative prediction of Umami recognition threshold - Zhiyong Cui; Yueming Wang; Tianxing Zhou; Jiaming Gu; Zhiwei Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Stable precursor-ink strategy for inkjet-printed high-temperature oxide films: Towards scalable ITO/In2O3 fabrication - Bian Tian; Jiaming Lei; Zhongkai Zhang; Yedi Zhou; Heng Li; Meng Wang; Shuimin Li; Xu Fan; Guoliang Zhou; Zhaojun Liu; Peng Shi (Chemical Engineering Journal, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Direct electrospinning of super fatigue resistant and fire-retardant aerogels for thermal insulation - Lingyun Wu; Jiaming Li; Yunfang Liu; Manxi Zhou; Dan Xue; Gang Bai; Aosong Zhou; Xiaoping Yang; Gang Sui (Chemical Engineering Journal, 2025)

An in-situ generated multiphase catalyst for active and durable ammonia protonic ceramic fuel cells - Haiyang Lan; Zixuan Xue; Jiakun Sun; Jiaming Chu; Jiangyuan Feng; Weitao Jin; Zixian Wang; Ruiqing Song; Pengfei Yan; Liang Zhang; Yucun Zhou; Xiaofeng Ye; et al. (Chemical Engineering Journal, 2025)

Investigation of nTiO2-WTe2 (n = 1–3) nanocluster sensors for the detection of toxic gases H2S, NH3, and NO2 in agricultural greenhouses: A DFT study - Haoming Zhang; Jiaming Jiang; Wen Zhou; Qu Zhou (Journal of Environmental Chemical Engineering, 2025)

Br− as a potential suppressor of NDMA formation during ozonation of HDMS: Mechanisms and implications - Fan Zhou; Menglan Gao; Xiaobin Liao; Jiaming Zhu; Zhenkun Chen; Huatong Ma; Huayu Zhang; Jin Wang; Chenyang Liao; Mingzhi Huang; Zhimin Yang (Chemical Engineering Journal, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Dynamic interplay between core functional microbial succession and flavor metabolite formation in naturally fermented sufu: A multi-omics perspective - Chen Chen; Jiaming Li; Zahoor Ahmed; Changyue Deng; Feng Wang; Jingwei Hu; Yibin Zhou (Food Bioscience, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

Emission Characteristics and Absorption Removal of Ultra-high Concentration NOx in an Arc-Heated Wind Tunnel - Zhiliang Xue; Jie Yuan; Jiaming Shao; Pei Li; Yonggang Zhou; Tao Zhu; Zhihua Wang (International Journal of Environmental Research, 2025)

Extraction of Chlorella polysaccharide using natural deep eutectic solvent - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Huiqing Zhang; Changhua Shang (Algal Research, 2025)

Dynamic response of seabed in wind power of deep-shallow sea induced by internal solitary waves - Jiaming Xiang; Zhuangcai Tian; Youkou Dong; Enjin Zhao; Lei Song; Jianhua Yue; Guoqing Zhou; Xiaolei Liu; Xiujun Guo; Yonggang Jia (Marine Georesources & Geotechnology, 2025)

3D printing programmed diagnostic and therapeutic bioactive “all-in-one” microspheres with multistimuli responsiveness for cartilage regeneration - Feifei Zhou; Wenjing Zhang; Yuan Yang; Shuyu Liu; Jing Long; Siqi Zhang; Jiaming Cui; Yuxiao Lai; Weimin Zhu (Chemical Engineering Journal, 2025)

Extraction, purification and antioxidant activity of Chlorella polysaccharide - Bingfeng Zhou; Jiaming Jiang; Yu Huo; Juying Lin; Changhua Shang (Algal Research, 2025)

The comparison of anticrystallization effects of cellulose derivatives with polyvinylpyrrolidone and poloxamer on andrographolide: In vitro and in vivo characterization - Xiaoyi Zhang; Peixia Luo; Jiaming Wang; Lei Yang; Zipei Pang; Shufeng Chen; Yi Zhou; Linghao Qin (Carbohydrate Polymers, 2025)

Study on the division method of the excavation disturbed zone in tunnels based on continuous-discontinuous theory - Jixu Zhang; Xiaodong Fu; Chao Tan; Yongqiang Zhou; Qian Sheng; Chen Xu; Jiaming Wu (Bulletin of Engineering Geology and the Environment, 2025)

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Structural characterization of archaeal GDGT cyclization: Linking physiological adaptation to paleotemperature reconstruction - Jiaming Zhou; Liang Dong (Earth and Planetary Science Letters, 2025)

Enhanced carbon dioxide capture via amphiphobic PVDF membrane modification for membrane contactors: Overcoming wettability challenges - Chang Li; Yanbin Yun; Fengguang Huang; Jiaming Mao; Jia Liu; Wenjuan Yang; Chunyun Zhou; Meng Li (Chemical Engineering Journal, 2025)

Engineering cuttlefish melanin nanoparticles: A dual-action therapy for acute radiation syndrome and combined radiation-wound injuries via regulating Bcl-2 family proteins and caspases in the apoptotic process - Zhemeng Zhao; Bin Hu; Danfeng Zhang; Xinyue Cui; Wen Ding; Tongshuai Wang; Jingyi Wang; Ziyi Guo; Yingtang Zhou; Shige Wang; Jiaming Guo (Chemical Engineering Journal, 2025)

Anhydrous deep eutectic solvents-based biphasic absorbents for efficient CO2 capture: Unravelling the critical role of hydrogen bond-mediated electron transfer - Jiaming Mao; Yunqian Ma; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Chunyun Zhou; Hongwei Xie; Yanbin Yun (Chemical Engineering Journal, 2025)

Ternary Fenton-like material (γ-Fe2O3/MoS2/PANI) supported on polysulfate membrane for high-performance catalytic degradation of tetracycline solution - Jiaming Xu; Heng Zhang; Lian-Biao Zhao; Xiaohong Xing; Junlan Tang; Xiangru Zhou; Lincheng Zhou (Journal of Water Process Engineering, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Cyclization: A potential effective modification strategy for umami peptides - Zhiyong Cui; Yanyang Yu; Tianxing Zhou; Chengliang Qi; Jiaming Gu; Ninglong Zhang; Xiaoxiao Feng; Zhiwei Zhang; Yiwen Zhu; Yin Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Efficient extraction of Spirulina phycocyanin using natural deep eutectic solvents and its characteristics - Juying Lin; Jiaming Jiang; Lei Mo; Yu Huo; Yan Pang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Development of dual polymerase spiral reaction for detection of Listeria monocytogenes and Staphylococcus aureus simultaneously - Moran Zhang; Hongzhou Chen; Jiaming Huang; Yongjin Dai; Yujuan Liu; Xiyao Zhou; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (International Journal of Food Microbiology, 2025)

A functional fluorine (F)-containing oxidiser of nano-networked NH4CuF3 to improve the combustion efficiency of Al powder - Xiandie Zhang; Haozhe Li; Xuxu Cui; Weiduo Fei; Xinwen Ma; Jiaming Liu; Pingyun Li; Xiaode Guo; Xiang Zhou (Fuel, 2025)

Fish Community Diversity and Spatiotemporal Dynamics in the Downstream of the Fujiang River Based on Environmental DNA - Jiaming Zhang; Yifang Chen; Xinxin Zhou; Jiaxin Huang; Xiaohan Dong; Shuli Zhu; Yanjun Shen (Fishes, 2025)
Hydrological changes caused by dam construction are among the primary drivers of global freshwater biodiversity decline. To assess the current status of fish community diversity and examine the impacts of cascade hydropower development on fish diversity, this study employed environmental DNA (eDNA) technology from 2023 to 2024 to conduct seasonal surveys at 18 sampling sites across six river segments separated by five dams in the downstream section of the Fujiang River. The study aimed to uncover the temporal and spatial dynamics of fish diversity and community structure, as well as to analyze the influence of environmental factors on these patterns. The results identified 84 fish species spanning 60 genera, 19 families, and 7 orders, including 2 nationally protected species, 11 endemic species of the upper Yangtze River, and 13 alien species. The cascade dams were found to have significantly reduced fish diversity compared to historical records, with a marked decline in native species and a rise in alien species, contributing to the miniaturization and homogenization of fish communities. Environmental factor analysis revealed that chemical oxygen demand (COD), dissolved oxygen (DO), total dissolved solids (TDS), electrical conductivity (EC), and reservoir formation time were significant drivers of fish community structure and diversity. This study provides essential baseline data on fish diversity under the influence of cascade hydropower development in the Fujiang River. It also offers valuable insights into the current status of fish resources and supports efforts in fish conservation and aquatic ecosystem management in the region.

Cell wall and reactive oxygen metabolism responses of stored Shine Muscat grapes to combined melatonin and 24-epibrassinolide treatment - Yaoying Zeng; Jiaming Zhang; Hui Su; Le Xie; Ye Zhao; Yubo Xiong; Zhou Wenhua (Postharvest Biology and Technology, 2025)

Effect of heat treatment on the stability of ultrasound-assisted cross-linked myofibrillar protein-stabilized emulsion filler phases via rheology and tribology - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Qi Wang; Zhen Li; Jingyu Wang; Xinglian Xu (Food Hydrocolloids, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Extraction, purification and characterization of Spirulina phycocyanin - Juying Lin; Yan Pang; Yu Huo; Jiaming Jiang; Bingfeng Zhou; Changhua Shang (Algal Research, 2025)

Insights into the effects of environmental factors on phytoplankton and microzooplankton at a basin scale: diversity, assembly mechanisms, and co-occurrence networks - Yanjun Shen; Xinxin Zhou; Jiaming Zhang; Qinghua Li; Yufeng Zhang; Qing Zuo (Frontiers in Marine Science, 2024)
Mastering the characteristics of planktonic microbial communities under the influence of basin-scale environmental factors can provide scientific basis to develop more targeted protection and restoration measures. Here, an environmental DNA metabarcoding technology was applied to investigate the phytoplankton and microzooplankton simultaneously along the whole basin of Jialing River, one of the most important rivers in Southwest China with large scale altitude gradient and water temperature discrepancy. Along the river-way from upper to lower reach, an upward trend in richness of both phytoplankton and microzooplankton was observed with significant positive and negative correlations to water temperature and altitude (Spearman correlation, p < 0.05), respectively. Significant variations in their compositions along the river were also uncovered with Chrysophyta and Foraminifera was potential keystones recognized by the co-occurrence network analysis. Additionally, exponential distance-decay of similarities were detected for both phytoplankton and microzooplankton, which were stronger for phytoplankton. Based on the results of variation partitioning analysis and null model, variations in phytoplankton communities were more governed by environmental selection than those in microzooplankton. Furthermore, the co-occurrence network showed a declining trend in the complexity and stability from the upper to lower reaches. These findings could serve to establish a basis for the investigation of phytoplankton and microzooplankton communities in rivers with multiple artificial modifications.

Environmental DNA (eDNA) reveals the effects of cascade dam development on the distribution patterns of aquatic biodiversity in mountain rivers - Yanjun Shen; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Ruli Cheng (Frontiers in Marine Science, 2024)
The rich and special biodiversity in mountain rivers is experiencing a continuous decline due to the influence of climate change and anthropogenic factors. To explore the alterations in the distribution of aquatic biodiversity in mountain rivers in the context of cascade dam development, the environmental DNA (eDNA) metabarcoding technique was used to examine the aquatic biodiversity of the Wujiang River, a representative mountain river with an 11-stage cascade dam. In this study, a comprehensive analysis of aquatic organisms in the Wujiang River mainstem was conducted, and 17 phyla and 38 classes were detected in the 36 water samples. The most abundant group is the benthic organisms, and the least abundant group is the amphibians. The results of the diversity analysis showed a clear longitudinal distribution pattern of aquatic organisms along the altitudinal gradient, with higher richness of aquatic organism communities the further to the lower reaches. Meanwhile, RDA analysis revealed that altitude, dissolved oxygen, reservoir length, and reservoir construction time were the key environmental factors influencing the distribution of aquatic organisms in the Wujiang River mainstem. The findings of this research also showed the applicability of the eDNA method in detecting aquatic biodiversity.

Trajectory tracking PID passivity-based control of spacecraft formation flying around Sun-Earth L2 point in the port-Hamiltonian framework - Jiaming Wang; Qingrui Zhou; Wei Zheng; Jingdong Diao (Advances in Space Research, 2024)

Transport processes of dissolved and particulate nitrogen and phosphorus over urban road surface during rainfall runoff - Yang Xiao; Chi Zhang; Taotao Zhang; Bin Luan; Jiaming Liu; Qiang Zhou; Chentao Li; Haoke Cheng (Science of The Total Environment, 2024)

Structural insights linking H-bridging of archaeal GDGTs to high temperature - Jiaming Zhou; Liang Dong (Science of The Total Environment, 2024)

Southwest Boundary of Yangtze and Cathaysia Blocks: Constraints from the Luojiashan Gabbro in Yingyangguan Region, Northeastern Guangxi - Ya Qin; Zuohai Feng; Jiaming Zhu; Yonggao Huang; Jie Wu; Yun Zhou; Yunfeng Xue; Chunzeng Wang (Journal of Earth Science, 2024)

Application of rheology and interfacial rheology to investigate the emulsion stability of ultrasound-assisted cross-linked myofibrillar protein: Effects of oil phase types - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Weiyi Zhang; Xinglian Xu (Food Hydrocolloids, 2024)

Intelligent design method of mine tunnel portal driven by knowledge graph - Jiaming Wu; Mingqing Xiao; Linfabao Dai; Huajun Bo; Zhixiang Lian; Hao Zhou; Jian Yang; Jianwei Pu; Hongzhan Cheng (Computers and Geotechnics, 2024)

Erratum to: Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Effects and mechanisms of ultrasound-assisted emulsification treatment on the curcumin delivery and digestive properties of myofibrillar protein-carboxymethyl cellulose complex emulsion gel - Lei Zhou; Jiaming Cai; Jingyu Wang; Chao Ma; Lujuan Xing; Siah Ying Tang; Wangang Zhang (Food Research International, 2024)

A study on ice resistance prediction based on deep learning data generation method - Qianyang Sun; Jiaming Chen; Li Zhou; Shifeng Ding; Sen Han (Ocean Engineering, 2024)

eDNA reveals spatial homogenization of fish diversity in a mountain river affected by a reservoir cascade - Ruli Cheng; Xinxin Zhou; Yufeng Zhang; Qinghua Li; Jiaming Zhang; Yang Luo; Qiliang Chen; Zhihao Liu; Yingwen Li; Yanjun Shen (Journal of Environmental Management, 2024)

Effects of improper emergency mitigations on a large-scale landslide triggered by road excavation: A case study of the Fengping landslide, Hubei province, China - Yi Luo; Jiaming Zhang; Zhi Zhou; Guosheng Jiang; Modong Duan (Bulletin of Engineering Geology and the Environment, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

An intelligent control method for PEMFC air supply subsystem to optimize dynamic response performance - Qingqing Su; Jiaming Zhou; Fengyan Yi; Donghai Hu; Dagang Lu; Guangping Wu; Caizhi Zhang; Bo Deng; Deming Cao (Fuel, 2024)

Effect of Yamadazyma triangularis derived peptide XHY69AP on muscle fatigue via regulation of AMPK/PGC-1α and Nrf2/Keap1 pathways - Jiaming Cai; Ye Tao; Lujuan Xing; Lei Zhou; Ming Ju; Wangang Zhang (Food Bioscience, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Cavity effects on spontaneous ignition of pressurized hydrogen jets - Jiaxin Zhang; Jiaming Huang; Qingxin Ba; Bo Zhou; David M. Christopher; Ming Gao; Xuefang Li (Fuel, 2024)

Effects of ultrasound-assisted emulsification and carboxymethyl cellulose addition on the rheological and microstructure properties of myofibrillar protein-soybean oil emulsion gel - Lei Zhou; Dacheng Kang; Jingyu Wang; Jiaming Cai; Lujuan Xing; Wangang Zhang (Food and Bioproducts Processing, 2024)

Image-guided structure-constrained inversion of electrical resistivity data for improving contaminations characterization - Xinmin Ma; Jieyi Zhou; Jing Li; Jiaming Zhang; Chunmei Han; Lili Guo; Shupeng Li; Deqiang Mao (Computers & Geosciences, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Energetic characteristics of highly reactive Si nanoparticles prepared by magnesiothermic reduction of mesoporous SiO2 - Xinwen Ma; Weiduo Fei; Jiaming Liu; Xiandie Zhang; Jie Ji; Xiang Zhou (Chemical Engineering Journal, 2024)

Exploring the relationship between the interfacial properties and emulsion properties of ultrasound-assisted cross-linked myofibrillar protein - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Zongyun Yang; Xinglian Xu (Food Hydrocolloids, 2024)

Cas-Rainbow: Cas12a-driven single-reaction multiplex detection system - Yuqing Zhu; Jianming Zhou; Yuxin Liang; Yao Lu; Shujun Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2024)

Molecular dynamics simulations reveal methylation in Me-GDGTs as a microbial low-temperature adaptation - Jiaming Zhou; Liang Dong (Chemical Geology, 2024)

Recent advances in nanomaterial-enhanced persulfate activation for organic pollutants removal: Electron transfer, surface reactions, and radical generation - Dingren Ma; Ji Mei; Qiwen Liang; Yimu Jiao; Tianyu Hu; Jingchen Chen; Jiaming Wang; Hao Zhou; Qiyu Lian; Mingzhe Sun; Dehua Xia; Tianqi Wang (Journal of Environmental Chemical Engineering, 2023)

A shining transmutation of lignin into multicolor carbon dots via the dynamic solvent-fractionation engineering - Xinyan Hou; Jikun Xu; Pengfei Zhou; Lin Dai; Jiaming Zhang; Xiao Xiao; Kaifu Huo (Chemical Engineering Journal, 2023)

Insights into chloride sorption and phase transformation of the synthesized Ca-Al bimetallic oxides in flue gas desulfurization wastewater - Zhen Zhou; Qiaoling Zhu; Ziwei Lan; Yuyue Yang; Li Zeng; Chengrui Liu; Jiaming Guo; Xiaodan Zhao (Chemical Engineering Journal, 2023)

A dual amplification-based CRISPR/Cas12a biosensor for sensitive detection of miRNA in prostate cancer - Yuqing Zhu; Xiaohe Zheng; Shujun Zhou; Wenjing Xiao; Xiaorui Sun; Jianming Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Analytica Chimica Acta, 2023)

Comparing extraction methods for analyzing n-alkyl lipids in shelf sediments from the China Sea - Jiaming Zhou; Xiaoxiao Zhao; Xin Chen; Liang Dong (Organic Geochemistry, 2023)

Visible-light photocatalytic degradation of water-soluble polyvinyl alcohol in aqueous solution by Cu2O@TiO2: Optimization of conditions, mechanisms and toxicity analysis - Jiaming Zhang; Zhenqi Zhou; Bing Xiao; Chenxu Zhou; Zhongqin Jiang; Yinna Liang; Zhuo Sun; Jianhua Xiong; Guoning Chen; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Management, 2023)

Responses of sediment nitrogen forms and bacterial communities to different aquatic nitrogen conditions in three submerged macrophyte-type ecological treatment systems - Xinyan Zhou; Tiehan Cheng; Jiaming Yu; Mengting Sheng; Xuelian Ma; Yucheng Cao (Environmental Research, 2023)

Full-scale experimental study on evacuation behavior characteristics of underwater road tunnel with evacuation stairs under blocked conditions - Kunkun Chu; Baochao Xie; Zhisheng Xu; Dan Zhou; Lu He; Jiaming Zhao; Houlin Ying (Tunnelling and Underground Space Technology, 2023)

Shrub encroachment increases soil organic and inorganic carbon in coastal wetlands - Shiwei Zhou; Ling Meng; Yuru Wu; Jiaming Kong; Xiaoli Bi (Journal of Soils and Sediments, 2023)

Four new terpenoids and other metabolites with potential anti-complementary activities from the aerial parts of Dracocephalum moldavica (Lamiaceae) - Jiaming Wang; Jinfeng Sun; Long Jin; Yanyan Huang; Mengjie Wang; Mei Jin; Shengbao Diao; Wei Zhou; Gao Li (Natural Product Research, 2023)

Magnetic field assisted process for preparing anti-biofouling PVDF membranes incorporated by hydrophilic magnetic palygorskite - Hengyang Mao; Jiayun Zhu; Shouyong Zhou; Jiaming Wang; Mengting Li; Ailian Xue; Meisheng Li; Yijiang Zhao; Wenbo Peng; Weihong Xing (Applied Clay Science, 2023)

Effects of Dietary Lentinus edodes Fermentation Supplementation on Digestive Enzyme Activity, Antioxidant Capacity and Morphology of the Liver and Intestine in Largemouth Bass (Micropterus salmoides) Fed High Plant Protein Diets - Jiaming Xu; Zhoulin Yu; Guangye Liu; Sijie Li; Guoyong Zhou; Hanhua Wang; Yewei Dong; Cuihong You; Weidong Bai; Meng Zhou; Yanhua Huang; Xiaohong Tan (Fishes, 2023)
This study evaluated the effect of Lentinus edodes fermentation (LEF) on digestive enzyme activity, antioxidant capacity and morphology of the liver and intestine in largemouth bass (Micropterus salmoides) fed high plant protein diets (HPPD). LEF was supplemented in HPPD with 0 g kg−1 (LEF0), 10 g kg−1 (LEF1), 20 g kg−1 (LEF2), 30 g kg−1 (LEF3), 40 g kg−1 (LEF4), 50 g kg−1 (LEF5), respectively, and then the six diets were fed to largemouth bass with a body weight of 28.8 ± 0.05 g for eight weeks. Juvenile fish were randomized into 6 groups and each group had 4 replicates with 40 fish. Dietary LEF supplementation alleviated the liver inflammatory reaction of largemouth bass caused by HPPD and improved liver morphology. Goblet cells multiplied and the gut muscle layer thickened after LEF supplementation. The LEF significantly increased amylase activity in the liver and intestine of largemouth bass in individual experimental groups. The LEF could increase the activity of catalase in the liver and intestine of largemouth bass (p

Efficient separation and comprehensive extraction of aluminum, silicon, and iron from coal fly ash by a cascade extraction method - Xiaodan Zhao; Li Zeng; Jiaming Guo; Qiaoling Zhu; Zhuojun Huang; Lifeng Lin; Xuanang Chen; Jing Cao; Zhen Zhou (Journal of Cleaner Production, 2023)

Effects of carboxymethyl cellulose on the emulsifying, gel and digestive properties of myofibrillar protein-soybean oil emulsion - Lei Zhou; Jinyuan Jiang; Fan Feng; Jingyu Wang; Jiaming Cai; Lujuan Xing; Guanghong Zhou; Wangang Zhang (Carbohydrate Polymers, 2023)

MLKL and other necroptosis-related genes promote the tumor immune cell infiltration, guiding for the administration of immunotherapy in bladder urothelial carcinoma - Boqiang Zhong; Youzhi Wang; Yihao Liao; Jiaming Liang; Keke Wang; Diansheng Zhou; Yang Zhao; Ning Jiang (Apoptosis, 2023)
The involvement of necroptosis in the immunosuppressive tumor microenvironment has been established and has been shown to contribute to the growth of pancreatic ductal adenocarcinoma, indicating its role in promoting tumor development. However, the relationship between necroptosis and bladder urothelial carcinoma (BUC) has yet to be fully understood. To shed light on this issue, our study aimed to uncover the impact of necroptosis on immune cell infiltration and immunotherapy response in BUC patients. We conducted an analysis of 67 necroptosis genes to assess their expression and genomic changes across pan-cancer and identified 12 necroptosis genes that are prognostically relevant and associated with immune subtypes and tumor stemness in BUC. Using a public database of 1841 BUC samples, we then performed Unsupervised Cluster Analysis and discovered two distinct necroptotic phenotypes in BUC. These phenotypes showed significant differences in molecular subtypes, immune infiltration patterns, and gene mutation profiles. We confirmed this discovery in BUC through qPCR and WB experiments. To evaluate the impact of necroptosis on prognosis, chemotherapy sensitivity, and immunotherapy response (such as anti-PD-L1), we developed a principal component analysis model called NecroScore. Finally, we validated the effects of RIPK3 and MLKL through a nude mouse transplantation model for BUC. Our study has uncovered that necroptosis plays a role in shaping the tumor immune microenvironment in BUC. The high necroptosis phenotype (Cluster B) was characterized by a higher abundance of tumor immunosuppressive cells and more key biological processes driving tumor progression, while the low necroptosis group (Cluster A) had higher FGFR3 mutations. We found that the infiltration levels of immune cells, including CD8+ T cells, were significantly different between FGFR3 mutated and wild-type (WT) samples. Our results confirmed the reliability of NecroScore as a comprehensive assessment tool for evaluating the immunotherapeutic effect and prognosis of BUC patients, with high NecroScore values favoring basal-like differentiation and lower FGFR3 alterations. We also observed that high expression of MLKL had a significant inhibitory effect on tumor growth and increased neutrophil infiltration in vivo. In our study, we uncovered the regulation pattern of necroptosis in the tumor immune microenvironment of BUC. Additionally, we developed a scoring tool called NecroScore that can be utilized to predict the most suitable chemotherapy and immunotherapy strategy for bladder urothelial carcinoma patients. This tool can effectively guide the chemotherapy and immunotherapy regimens for patients with advanced BUC.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A data-driven support system for the efficient schedule delay management of the ultra-high-voltage projects considering subjective risk preferences - Yunna Wu; Jiaming He; Yijia Liao; Yao Tao; Fangtong Liu; Jianli Zhou (Sustainable Cities and Society, 2023)

Dynamic response of single-bucket foundation in clay under vertical variable amplitude cyclic loadings - Hailei Kou; Weiwei Fang; Nan Zhou; Jiaming Huang; Xixin Zhang (Ocean Engineering, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Hepatoprotective Effects of Taurine Against Cadmium-Induced Liver Injury in Female Mice - Jiaming Zheng; Guobin Qiu; Yewen Zhou; Kezhe Ma; Sheng Cui (Biological Trace Element Research, 2023)

Optimization of a compact on-site stormwater runoff treatment system: Process performance and reactor design - Yangjie Qin; Chuanting Zhou; Siqi Yu; Hongjian Pang; Jiaming Guo; Jun Wei; Libing Wang; Yunxin Xing; Ying An; Zhen Zhou (Chemosphere, 2023)

Chemical constituents from the leaves of psidium guajava linn. and their chemotaxonomic significance - Guangxin Zhou; Jiaming Zhao; Chang Gong; Jixuan Xu; Ce Song; Dali Meng (Natural Product Research, 2023)

A new monoterpenoid glycoside and a new phenolic glycoside isolated from Dracocephalum moldavica and their anti-complementary activity - Jiaming Wang; Jinfeng Sun; Long Jin; Mengjie Wang; Yanyan Huang; Mei Jin; Wei Zhou; Gao Li (Natural Product Research, 2023)

Chlorine dioxide bleaching wastewater degradation in intimately coupled photocatalysis and functional bacteria: The roles of adsorption, photocatalysis, and biotransformation - Yinna Liang; Maman Galandi Abdoulaye; Chenxu Zhou; Bing Xiao; Jiaming Zhang; Jianhua Xiong; Qifeng Yang; J.R. Zhao; Shuangfei Wang (Journal of Cleaner Production, 2023)

Generation of reactive oxygen species through dissolved oxygen activation on defected porous carbon for efficient degradation of antibiotics - Jiaming Liu; Zhangwei Yao; Genping Qiu; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; Wenjing Yuan; Peihai Ju; Ruixi Lin; Hengcheng Zhou; et al. (Chemical Engineering Journal, 2023)

Ultrasonic assisted preparation of ultrafine Pd supported on NiFe-layered double hydroxides for p-nitrophenol degradation - Xuan Zhou; Jiaming Shi; Xuefeng Bai (Environmental Science and Pollution Research, 2022)

Effects of nitrogen addition on soil faunal abundance: A global meta‐analysis - Junxi Hu; Shixing Zhou; Liehua Tie; Xiong Liu; Xing Liu; Anjiu Zhao; Jiaming Lai; Lin Xiao; Chengming You; Congde Huang (Global Ecology and Biogeography, 2022)
Aim Soil fauna has a wide range of ecosystem functions. Anthropogenic atmospheric nitrogen (N) deposition affects the structure and function of soil fauna by changing the microenvironment and resources. Given that soil faunal responses can vary considerably among taxonomic groups, N deposition rate, and ecosystems, however, there is little consensus. We aimed to evaluate the effects of N deposition on different soil faunal taxa across different terrestrial ecosystems. Location Global. Time period 1970–2021. Major taxa studied Soil fauna. Methods We conducted a meta‐analysis that yielded 264 observations from 43 publications. We evaluated the responses to N addition of soil faunal abundance for three different taxa (nematodes, mites, collembolans) in three ecosystem types (cropland, forest, and grassland). Results Our results showed an overall negative effect of N addition on soil fauna. However, the effect varied among soil faunal taxa. Specifically, N addition had no significant effects on the abundance of collembolans and mites in any ecosystem. On the other hand, N addition significantly reduced the abundance of all nematode trophic groups except bacterivores. The overall reduction of soil fauna is likely driven by the nematode response. The negative effects of N addition on nematode abundance were contingent on the N addition rate, N addition form, and ecosystem type. N addition decreased nematode abundance at N addition rates of more than 100 kg/ha/year. Inorganic N addition negatively affected nematode abundance. Finally, N addition had a greater adverse effect on nematodes in cropland and grassland compared to forest ecosystems. Main conclusions Our results demonstrate the overall negative effects of N addition on nematode abundance. Excessive N addition should be avoided in cropland and grassland management. Further, we suggest the application of organic fertilizer instead of inorganic fertilizer to minimize the N‐induced negative effects on soil nematodes.

Lack of Knowledge, the main Stumbling Block of Fertility Preservation Promotion in China - Meng Wang; Lixia Zhu; Hua Xiong; Jiaming Wang; Zhou Li; Liu Yang; Lei Jin; Qingsong Xi (Journal of Cancer Education, 2022)

Characteristics of a rapid landsliding area along Jinsha River revealed by multi-temporal remote sensing and its risks to Sichuan-Tibet railway - Jiaming Yao; Hengxing Lan; Langping Li; Yiming Cao; Yuming Wu; Yixing Zhang; Chaodong Zhou (Landslides, 2022)

Two new phenolic glycosides with anti-complementary activity from the roots of Sanguisorba officinalis L - Rongshen Wang; Jinfeng Sun; Mei Jin; Chao Ye; Jiaming Wang; Long Jin; Ying Jie Ma; Wei Zhou; Gao Li (Natural Product Research, 2021)

Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

Effects of High-Dose of Copper Amino Acid Complex on Laying Performance, Hematological and Biochemical Parameters, Organ Index, and Histopathology in Laying Hens - Qin Zhou; Jiaming Zhu; Bing Liu; Jialing Qiu; Xintao Lu; Brian Curtin; Fei Ji; Dongyou Yu (Biological Trace Element Research, 2021)

Failure mechanism of a slow-moving landslide on September 27, 2020, in Chang Nong Village, Guangxi, China - Jiaming Zhang; Zhi Zhou; Feng Lin; Qinggang Yang; Yi Luo (Landslides, 2021)

Research on the rainfall-induced regional slope failures along the Yangtze River of Anhui, China - Jiaming Zhang; Yi Luo; Zhi Zhou; Chikhotkin Victor; Modong Duan (Landslides, 2021)

Two novel flavonoids from the leaves of Rhododendron dauricum L. with their inhibition of TNF-α production in LPS-induced RAW 264.7 cells - Chao Ye; Mei Jin; Chunshi Jin; Rongshen Wang; Jiaming Wang; Ying Zhang; Sainan Li; Jinfeng Sun; Wei Zhou; Gao Li (Natural Product Research, 2021)

A new pentacyclic triterpenoid from the leaves of Rhododendron dauricum L. with inhibition of NO production in LPS-induced RAW 264.7 cells - Jiaming Wang; Mei Jin; Chunshi Jin; Chao Ye; Yi Zhou; Rongshen Wang; Huanhuan Cui; Wei Zhou; Gao Li (Natural Product Research, 2020)

Large-Scale Test Model of the Progressive Deformation and Failure of Cracked Soil Slopes - Zhi Zhou; Jiaming Zhang; Fulong Ning; Yi Luo; Lily Chong; Kuangbiao Sun (Journal of Earth Science, 2020)

A Risk Assessment Method for Metro Shield Tunnel Construction Based on Interval Number - Yeqin Zhang; Jiaming Zhang; Hailin Guo; Yang Zhou; Guofu Ma; Cong Wang (Geotechnical and Geological Engineering, 2020)

Gene Biomarkers Derived from Clinical Data of Hepatocellular Carcinoma - Jiaming Qi; Jiaxing Zhou; Xu-Qing Tang; Yaolai Wang (Interdisciplinary Sciences: Computational Life Sciences, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)

Analysis of deformation characteristics for a reservoir landslide before and after impoundment by multiple D-InSAR observations at Jinshajiang River, China - Lingjing Li; Xin Yao; Jiaming Yao; Zhenkai Zhou; Xin Feng; Xinghong Liu (Natural Hazards, 2019)

Study of mosaicism of Pyropia yezoensis - Yuan He; Wei Zhou; Jiaming Li; Songdong Shen (Marine Biology Research, 2019)

The combination of osthole with baicalin protects mice from Staphylococcus aureus pneumonia - Shui Liu; Bowen Liu; Zhao-Qing Luo; Jiaming Qiu; Xuan Zhou; Gen Li; Bing Zhang; Xuming Deng; Zhenguo Yang; Jianfeng Wang (World Journal of Microbiology and Biotechnology, 2017)

Stacking S5-n and f5-n to overcome sterility in indica–japonica hybrid rice - Jiaming Mi; Guangwei Li; Jianyan Huang; Huihui Yu; Fasong Zhou; Qifa Zhang; Yidan Ouyang; Tongmin Mou (Theoretical and Applied Genetics, 2016)

Synergistic effect of EMS1-shRNA and sorafenib on proliferation, migration, invasion and endocytosis of SMMC-7721 - Jiaming Zhou; Li Chen; Yixin Zhang; Yuanyuan Wu; Guilan Wang; Song He; Zhongying Guo; Yingze Wei (Journal of Molecular Histology, 2014)

Clinical Analysis of 15 Cases of Liver Nodular Regenerative Hyperplasia - Tao Guo; Jiaming Qian; Liming Zhu; Weixun Zhou; Feng Zhu; Gang Sun; Xiucai Fang (Cell Biochemistry and Biophysics, 2012)